Validation and Reliability of The Frontal Assesment Battery (FAB) in Turkish - Tuncay, Nilgün; Kayserili, Gül; Eser, Erhan; Zorlu, Yaşar; Akdede, Berna Binnur; Yener, Gö (Journal Neurological Sciences, Ege Univ Hosp. Fac Med, Dept Neurosurgery, Bornova-Izmir, Tr35100, Turkey, 2013)
Scientific background: The Frontal Assessment Battery (FAB) test is a short test aiming to assess frontal lobe functions. It is composed of 6 items that give a total possible score between 0 and 18. The items include assessing the ability to find similarities between objects, categorical verbal fluency, resistance to interference, a simple go-no go paradigm, and peripheral autonomy. A higher score denotes better performance. Purpose: To determine the validity and reliability of the psychometric properties of the Turkish version of the Frontal Assessment Battery Method: The Turkish FAB was evaluated in 94 cases with diverse neuro-psychological conditions and in 92 healthy controls. Translation and back-translations of Turkish were done. In addition to FAB, the respondents completed a Standardized Mini Mental assessment scale, Stroop scale and a brief sociodemographic questionnaire. Reliability analysis involved test-retest reliability and internal consistency (alpha), whereas validity analysis involved factor analysis, convergent validity approach, known groups and criterion validity tests, and sensitivity analysis. Parametric and non-parametric correlations, T tests and ANOVA were used during these analyses. Findings: The alpha value was sufficient (alpha=0.73) for FAB but the alpha value decreased when the 6th item was deleted, indicating a problem with this item, as also confirmed by the factor solution. The fewer the years of education, the worse the FAB scale scores (p<0.001); men scored higher than women in a few items (mental flexibility, sensitivity to interference, and inhibitory control). The relationship between FAB and the Standardized Mini Mental Test (0.765, p<0.000) and Stroop scores indicated.
Keywords: K Frontal Cognition; FAB; Cross-Cultural Validation; Turkish; Frontotemporal Dementia; Parkinsons-Disease; Alzheimers-Disease; Japanese Version; Diagnosis; Validity